As cibercidades brasileiras: uma análise do panorama brasileiro de plataformas digitais, através do design - Saldanha, Leandra Dezotti (Universidade do Vale do Rio dos Sinos, 2013)
The research topic of this master's project addresses how contemporary cities are developing in relation to new technologies of information and communication and how to use digital platforms for promoting its image, to be inserted in the context of cybercities. The research undertaken is a multiple case study, focusing on the Brazilian capitals and on digital platforms that represent them, whether governmental, tourist, social or collaborative. This analysis takes into account the existing global reference models and theoretical studies already undertaken on cybercities, especially with regard to models cybercities, de Lemos (2002) and platform architecture of the cybercity, developed by Ishida (2002) to Kyoto in order to obtain data and analysis can weave an overview of how cybercities are structured in Brazil, searching through these results, comparative format and contextualize existing problems through the design of strategic vision, generating data for new studies how design can work on building strategic towns in the digital universe.
Keywords: Plataformas digitais; Redes; Cibercidades e design estratégico; Digital platforms; Networks; Strategic design cibercidades; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial